2016
DOI: 10.1136/bmjresp-2016-000166
|View full text |Cite
|
Sign up to set email alerts
|

Differential eligibility of African American and European American lung cancer cases using LDCT screening guidelines

Abstract: IntroductionLung cancer incidence and mortality is higher among African Americans compared with European Americans in the USA where screening guidelines are currently in place and based on age at diagnosis and smoking history. Given the different smoking patterns observed in these populations and the earlier age at which African Americans are diagnosed, it is possible that African Americans will be disproportionally excluded from screening programmes.MethodsWe assessed the capture of African American and EA lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 15 publications
(13 reference statements)
1
23
0
Order By: Relevance
“…These differences highlight the importance of identifying additional lung cancer risk factors that may disproportionately impact blacks or other vulnerable populations. Multiple investigators have suggested, for example, that black patients would benefit from race-specific adjustment of screening eligibility criteria [22,48,49]. Future research is needed to confirm the preliminary trends identified in this study.…”
Section: Discussionmentioning
confidence: 62%
“…These differences highlight the importance of identifying additional lung cancer risk factors that may disproportionately impact blacks or other vulnerable populations. Multiple investigators have suggested, for example, that black patients would benefit from race-specific adjustment of screening eligibility criteria [22,48,49]. Future research is needed to confirm the preliminary trends identified in this study.…”
Section: Discussionmentioning
confidence: 62%
“…22 Our results were consistent with previous studies and support the differential eligibility and exclusion of African American smokers from screening opportunities based on different risk profiles between these racial populations. 10,15,23 Ryan 15 found that a greater proportion of white smokers would be captured with current screening guidelines compared with African American smokers. Pinsky and Kramer 23 analyzed National Health Interview Survey and Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial data and found that the percentage of screening-eligible minority groups and women smokers greatly increased by reducing the selection criteria to include 20-to 29pack-year smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Although smoking prevention and cessation are the most effective interventions in reducing lung cancer incidence and mortality ( 18 ), the implementation and dissemination of high-quality LCS is poised to have a significant effect on reducing lung cancer deaths. However, current USPSTF guidelines do not take into account racial, ethnic, socioeconomic, or sex-based differences in smoking patterns and lung cancer risk and may not optimally select high-risk populations such as underrepresented minorities, PLHIV, or women who have increased lung cancer risk but a lower-intensity smoking history than men ( 4 , 19 21 ). A recent study used prediction models to simulate lifetime lung cancer risk and evaluated screening eligibility by USPSTF guidelines and by risk-based criteria (1.3–2.5% risk threshold) for younger (50–54 yr) and older (71–80 yr) individuals ( 22 ).…”
Section: Introductionmentioning
confidence: 99%